2D Gadolinium Oxide Nanoplates as T1 Magnetic Resonance Imaging Contrast Agents. Issue 11 (21st April 2021) - Stinnett, Gary; Taheri, Nasim; Villanova, Jake; Bohloul, Arash; Guo, Xiaoting; Esposito, Edward P.; Xiao, Zhen; Stueber, Deanna; Avendano, Carolina; Decuzzi, Paolo; Pautler, Robia G.; Colvin, Vicki L.
Abstract: Millions of people a year receive magnetic resonance imaging (MRI) contrast agents for the diagnosis of conditions as diverse as fatty liver disease and cancer. Gadolinium chelates, which provide preferred T 1 contrast, are the current standard but face an uncertain future due to increasing concerns about their nephrogenic toxicity as well as poor performance in high‐field MRI scanners. Gadolinium‐containing nanocrystals are interesting alternatives as they bypass the kidneys and can offer the possibility of both intracellular accumulation and active targeting. Nanocrystal contrast performance is notably limited, however, as their organic coatings block water from close interactions with surface Gadoliniums. Here, these steric barriers to water exchange are minimized through shape engineering of plate‐like nanocrystals that possess accessible Gadoliniums at their edges. Sulfonated surface polymers promote second‐sphere relaxation processes that contribute remarkable contrast even at the highest fields ( r 1 = 32.6 × 10 −3 m Gd −1 s −1 at 9.4 T). These noncytotoxic materials release no detectable free Gadolinium even under mild acidic conditions. They preferentially accumulate in the liver of mice with a circulation half‐life 50% longer than commercial agents. These features allow these T 1 MRI contrast agents to be applied for the first time to the ex vivo detection of nonalcoholic fatty liver disease in mice. Abstract : 2D Gadolinium oxide nanoplates are ideal candidates for T 1 magnetic resonance imaging contrast agents. With their vacant edges and novel sulfonated‐polymeric surface coating, these nanoplates demonstrate exceptional colloidal stability and high‐field relaxometric performance. These features allow these nanoscale T 1 MRI contrast agents to be applied to the ex vivo detection of nonalcoholic fatty liver disease in mice.